Pengaruh Digital Payment Dan Literasi Keuangan Terhadap Perilaku Konsumtif Dengan Gaya Hidup Sebagai Variabel Mediasi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Negeri Jakarta Angkatan Tahun 2021 - Intan Nur Aini; Tuty Sariwulan; Siti Fatimah Zahra (INDO PUBLISHING, 2026)
This study aims to examine the influence of digital payment usage and financial literacy on students’ consumptive behavior, with lifestyle as a mediating variable. The quantitative survey was conducted on 279 students of the Faculty of Economics and Business, Universitas Negeri Jakarta, class of 2021. Data were collected through questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results indicate that digital payment has a positive and significant effect on students’ consumptive behavior, both directly and through lifestyle mediation, due to the convenience and perceived benefits of digital payment. Financial literacy has a negative effect on consumptive behavior, both directly and through lifestyle, suggesting that higher financial literacy can reduce students’ tendency to be consumptive. The direct effect of financial literacy on consumptive behavior is more dominant than its indirect effect through lifestyle. Based on these findings, it is recommended that universities integrate financial literacy education into curricula and supporting activities, families provide financial management education from an early stage, and digital payment providers offer features that support students’ financial control. These strategies are expected to help students optimize the benefits of digital payment technology without increasing consumptive behavior.